The influence of roller burnishing process on hardness and roughness of cylindrical polymer surfaces - Brevern, P V; Low, K O; El-Tayeb, N S M (PROFESSIONAL ENGINEERING PUBLISHING LTD, 2008)
In the present study, the potential for using the roller burnishing process to improve Surface roughness and hardness of thermoplastics (acetal homopolymer, POM-H) and thermosets (polvurethane, PU) is investigated. The effect of roller burnishing parameters Such as burnishing force, speed, feed, and roller width contact is studied.